2019
DOI: 10.1051/radiopro/2019002
|View full text |Cite
|
Sign up to set email alerts
|

Skin protection against UV radiation using thin films of cerium oxide

Abstract: In this work, we evaluated the efficiency of cerium oxide as sunscreen using titanium oxide as standard comparison material. Geant4 software was used to perform numerical simulation, we calculated the radiation dose that ultraviolet radiation deposits in a skin sample as a function of thin film thickness of the sunscreens. We found that in the interval between 5 and 15 nm of the thin film thickness and for wavelengths between 160 and 400 nm, cerium oxide has the potential to reduce the radiation dose more than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…The main issues for organic UV filters are related to narrow UV absorbance, insufficient photostability, and toxicity, , whereas inorganic UV filters, such as TiO 2 , ZnO, and CeO 2 , are broad UV absorbers and highly photostable. Unlike larger inorganic particles that can leave behind a chalky white residue, metal oxide nanoparticles (NPs) offer transparency, but concerns regarding nanosafety and photocatalytic activity exist . Overall, the use of inorganic UV blockers may be preferable considering recent studies linking the bleaching of coral reef to organic UV filters in sunscreens , and other studies showing the promise of CeO 2 NPs in skin protection. …”
Section: Introductionmentioning
confidence: 99%
“…The main issues for organic UV filters are related to narrow UV absorbance, insufficient photostability, and toxicity, , whereas inorganic UV filters, such as TiO 2 , ZnO, and CeO 2 , are broad UV absorbers and highly photostable. Unlike larger inorganic particles that can leave behind a chalky white residue, metal oxide nanoparticles (NPs) offer transparency, but concerns regarding nanosafety and photocatalytic activity exist . Overall, the use of inorganic UV blockers may be preferable considering recent studies linking the bleaching of coral reef to organic UV filters in sunscreens , and other studies showing the promise of CeO 2 NPs in skin protection. …”
Section: Introductionmentioning
confidence: 99%
“…Similar SPF and UV‐shielding were observed for CeO 2 and TiO 2 , however, great improvement in photocatalytic activities and reduction of free radical generation were obtained by Ca 2+ coated CeO 2 nanoparticles 21 . In silico studies compared CeO 2 and TiO 2 films between 5 and 15 nm thick and showed that CeO 2 reduced the radiation dose more than 10% when compared to TiO 2 22 . Despite the necessity of tests to evaluate the stability, performance, and interaction with organic UV filters, CeO 2 showed a great potential as active ingredient.…”
Section: Cerium Dioxidementioning
confidence: 99%